2012
DOI: 10.1262/jrd.11-050m
|View full text |Cite
|
Sign up to set email alerts
|

Normal Calves Produced After Transfer of Embryos Cultured in a Chemically Defined Medium Supplemented with Epidermal Growth Factor and Insulin-like Growth Factor I Following Ovum Pick Up and <i>In Vitro</i> Fertilization in Japanese Black Cows

Abstract: Abstract. The objective of this study was to examine whether high concentrations of epidermal growth factor (EGF) and/or insulin-like growth factor I (IGF-I) would have a beneficial effect on bovine embryo development in vitro and to obtain normal calves by using an ovum pick up method and embryo culture in a chemically defined medium. When compared with controls, EGF (100 or 200 ng/ml) or IGF-I (50 or 100 ng/ml) significantly increased the rate of embryos that developed into blastocysts during an 8-day cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
4
21
1
Order By: Relevance
“…In line with our results, Brice et al (1993) hypothesised that EGF receptor seemed to be more linked to the regulation of TE differentiation rather than cell proliferation in mouse preimplantation embryos. In agreement with our results but with larger groups of bovine embryos in culture (20 embryos/100 ml), a recent work found a significant effect of the combination IGF-I and EGF on embryo development in comparison with non-GF-supplemented (Sakagami et al, 2012). With regard to total cells per embryo, supplementation of IGF-I and EGF did not increase total cell number per blastocyst, only the ICM cell number (Sakagami et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our results, Brice et al (1993) hypothesised that EGF receptor seemed to be more linked to the regulation of TE differentiation rather than cell proliferation in mouse preimplantation embryos. In agreement with our results but with larger groups of bovine embryos in culture (20 embryos/100 ml), a recent work found a significant effect of the combination IGF-I and EGF on embryo development in comparison with non-GF-supplemented (Sakagami et al, 2012). With regard to total cells per embryo, supplementation of IGF-I and EGF did not increase total cell number per blastocyst, only the ICM cell number (Sakagami et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results but with larger groups of bovine embryos in culture (20 embryos/100 ml), a recent work found a significant effect of the combination IGF-I and EGF on embryo development in comparison with non-GF-supplemented (Sakagami et al, 2012). With regard to total cells per embryo, supplementation of IGF-I and EGF did not increase total cell number per blastocyst, only the ICM cell number (Sakagami et al, 2012).On the other hand, the quality of embryos obtained at different days of culture was studied in the present work. We found that blastocyst at D7 had better quality, more cells per blastocyst and a lower apoptosis rate, than the rest of the blastocysts obtained later.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Actions of IGF1 on the preimplantation embryo indicate that both MAPK and PI3K/AKT pathways are activated (Figure 2). Culture with IGF1 increases the percent of embryos capable of developing to the blastocyst stage (28,30,(64)(65)(66)(67)(68)(69). This action of IGF1 probably involves increased proliferation because the cell number of day 6 morulae was increased by IGF1 (70).…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…These include insulin-like growth factor 1 (IGF1), epidermal growth factor (EGF), activin, granulocyte-macrophage colony-stimulating factor (GMCSF or CSF2), hyaluronan, fibroblast growth factor 2 (FGF2), and platelet-activating factor (PAF) (Gopichandran & Leese 2006, Fields et al 2011, Trigal et al 2011, Sakagami et al 2012). CSF2 has also been shown to act during gastrulation development (Loureiro et al 2009.…”
Section: Introductionmentioning
confidence: 99%